Academic and professional profile and impact of graduates from the Nephrology Graduate Program at UNIFESP - Pablo Ferraz; Nestor Schor; Gianna Mastroianni Kirsztajn (Brazilian Journal of Nephrology, 2025)
Abstract Introduction: Graduate studies in Brazil have experienced significant growth since the 1990s. Over a 40-year period, the Graduate Program in Nephrology at Unifesp has qualified 261 master’s graduates, 111 doctors and 146 individuals who completed both a master’s and a doctoral degree. Of these, 278 hold a degree in Medicine. Medical postgraduates were responsible for 124 master’s dissertations and 243 doctoral theses completed. Objective: This study analyzed the profile and professional trajectories of graduate students from the Nephrology Graduate Program at Unifesp. Methods: The authors used the university’s database to establish the graduates’ profile and applied a questionnaire to identify their professional performance in academia and the job market. The graduates were divided into three groups: G1 – 1976 to 1997 (N = 127); G2 – 1998 to 2006 (N = 150); G3 – 2007 to 2015 (N = 241). Results: Regarding sex, male medical graduates were responsible for 53.6% of all completion papers; however, in the most recent period, women accounted for 61% of the works. Female participation was consistently higher among graduates from other areas, at 73.8% of the total. Among the physicians, 65.5% graduated from public universities, with the first group standing out with 73%. In the other groups, 59.5% and 59.8% came from public HEIs, respectively. The overall average income reported by master’s graduates responding to the questionnaire ranged from 5 to 10 minimum wages (MW), and for doctors, above 10 MW. Conclusion: Doctoral graduates had a strong presence in academia, predominantly within the public sector.